Immunopathological Response Of Kids In Pneumonia - Anilkumar T V (Department of Pathology, College of Veterinary and Animal Sciences, 1986)
The immunopathological response of kids spontaneously affected with pneumonia and kids experimentally dosed with aflatoxin was evaluated, for the first time, employing various immunological markers. Attempts were also made to modulate the immune response of kids for the first time using levamisole. There was enhancement of the immune response in pneumonic kids as evidenced by leukocytic response, number of T-lymphocyte sub-population in the peripheral blood, in vitro neutrophil activity, concentration of gammaglobulin in the serum and cutaneous response to 2, 4-Dinitrochlorobenzene and phytohaemagglutinin. Immunological background of kids fed aflatoxin (at the rate of 0.25 mg/kg body weight) was evaluated, Immunostimulation (in first 15 days) was followed by immunosuppression (from 15 days until death). The kids developed pneumonia and died. It was concluded that at a dose rate of 0.25 mg/kg body weight aflatoxin caused immunosuppression in goates. At a dose rate of 3.75 mg/kg body weight (s/C) levamisole induced immunostimulation in kids. It did not cause immunomodulation in pneumonic kids.